2010
DOI: 10.1111/j.1398-9995.2009.02286.x
|View full text |Cite
|
Sign up to set email alerts
|

The allergen Bet v 1 in fractions of ambient air deviates from birch pollen counts

Abstract: In general, pollen count and allergen in ambient air follow the same temporal trends. However, because a 10-fold difference can exist in allergen potency of birch pollen, symptoms might be difficult to correlate with pollen counts, but perhaps better with allergen exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
110
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(121 citation statements)
references
References 41 publications
9
110
0
2
Order By: Relevance
“…Hopefully, availability of pollen allergen count on a daily basis, as is planned in the frame of the European HIALINE project (www.hialine.eu), could provide conclusive data on the actual changes in the allergenic load of the air during such an extreme precipitative event. Preliminary data have shown that although pollen count and allergen in ambient air follow the same temporal trends, a 10-fold difference can exist in allergen potency of birch pollen, so that symptoms might be difficult to correlate with pollen counts, but perhaps better with allergen exposure [34].…”
Section: Public Health Dimensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hopefully, availability of pollen allergen count on a daily basis, as is planned in the frame of the European HIALINE project (www.hialine.eu), could provide conclusive data on the actual changes in the allergenic load of the air during such an extreme precipitative event. Preliminary data have shown that although pollen count and allergen in ambient air follow the same temporal trends, a 10-fold difference can exist in allergen potency of birch pollen, so that symptoms might be difficult to correlate with pollen counts, but perhaps better with allergen exposure [34].…”
Section: Public Health Dimensionmentioning
confidence: 99%
“…In addition, real-time data on both weather forecasting and pollination are not available in many countries at present. Finally, despite the increasing amount of data about allergen content of ambient air published in recent years [34,35], to date, pollens or mould allergens have never been quantified during a thunderstorm. Hopefully, availability of pollen allergen count on a daily basis, as is planned in the frame of the European HIALINE project (www.hialine.eu), could provide conclusive data on the actual changes in the allergenic load of the air during such an extreme precipitative event.…”
Section: Public Health Dimensionmentioning
confidence: 99%
“…By means of ELISA the Bet v 1 load of the tested PM10 samples (n=8) was below the detection limit of 1.2 ng/ml (data not shown). Similarly, Buters and others identified no Bet v 1 in the PM <2.5 µm fraction and only about 7% in the 10 µm >PM >2.5 µm fraction, but more than 93% in the PM >10 µm fraction of ambient air 13 . The contrasting results of the ELISA on the one hand and the FACS analysis on the other hand, may be caused by differences in the detection method in conjunction with divergent sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…To date many studies examine the allergen content in ambient air particulate matter by extracting the respective allergen and subsequent quantification with ELISA 5,[12][13][14]17 . There is a fundamental difference between the procedure described here and the quantification with ELISA: ELISA quantifies the extracted and dissolved antigen, while flow cytometry analyzes the particle-bound antigen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation